Environmental Learning Using Interactive Media to Increase Coastal Local Knowledge About Environmental Problems Mitigation in Luwu Raya Sulawesi - Asri Asri; Rusdiana Junaid (Jurnal Studi Guru dan Pembelajaran, 2021)
This research aims to mitigate environmental problems through learning by using documentary films for fishermen groups whose environmental conditions have been damaged for years. The fishermen group were from Belopa, Harapan, and Munte Village, North Luwu Regency. The method used was action research by creating learning tools validated by two education experts in two learning actions to observe the learning components' feasibility. The validation of the learning plan and documentary film was in the "very valid" category, which means that these two tools are suitable for increasing environmental knowledge. Education experts also assessed that implementation of learning syntax components, social systems, reaction principles, and support systems was also "very valid." The learning outcome of the fishermen groups ware also improved. At the first action in Belopa, the students' levels were in the low and medium categories. Then at the second action, it increased to the medium and high categories. Meanwhile, at the first action in Harapan, the students' levels were in a low category. Furthermore, at the second action, it went up to the medium and high category. In Munte, the first action shows that the students' levels were in the low and medium categories. Then it increased to the medium and high category at the second action. Efforts to mitigate environmental problems through learning documentary films can increase fishermen groups' environmental knowledge in the low, medium, and high categories even it has not impacted the environment directly yet.